Efficient Liquid-Junction Monolithic Cobalt-Mediated Dye-Sensitized Solar Cells for Solar and Artificial Light Conversion - Fátima Santos (2021)
Due to the extremely high power conversion efficiency under indoor light, aesthetic appeal, and safety, the mature technology of dye-sensitized solar cells (DSSCs) is now considered as one of the most budding technologies to address the fast-growing need for cordless power in countless IoT devices and wireless sensors. The monolithic design of DSSCs (M-DSSCs) is technologically attractive for commercial production offering straightforward processing in-series modules, low cost, and compactness. The advancements in liquid-junction M-DSSCs reported so far are related only to conventional Ru-dye and I-3(-)/I- electrolyte devices. The present study reports a M-DSSC incorporating a Co(III)/(II)(bpy)(3) redox shuttle and a YD2-o-C8 porphyrin dye and developed using commercial materials. The apparent activation energy for electron transfer, electron charge-transfer resistance, and exchange current density on FTO-Pt nanoparticles, Pt metal, graphite/carbon-black, and PEDOT:PSS in the cobalt electrolyte were determined to identify the favorable counter-electrode. The impact of the electrical spacer layers made from conventional ZrO2 and highly reflective rutile TiO2 on the photocurrent quantum yield was also assessed. The recombination-suppressing additive concentration in the electrolyte and photoanode sensitization conditions were thoroughly optimized to render M-DSSC devices with a photocurrent conversion efficiency of 9.5% under 1-sun illumination, which is by far the highest reported for M-DSSCs. The high power conversion efficiency of ca. 22% was attained under 1000 lx artificial light, making the developed M-DSSCs very attractive for indoor use.